An occupational health survey on health utility and occupational diseases in Chinese university staff to inform cost-utility analysis - Xiaoyan Liu; Xiaoyan Liu; Huijun Zhou; Jie Wei; Minghui Li; Guofen Luo; Nasheen Naidoo; Guang Zhang; Ye Bi; Mengmeng Gao (Frontiers Media S.A., 2023)
BackgroundThe occupational health of university staff bears great social and economic value for which health utility is an indivisible aspect. Utility is also the primary data for the cost-utility analysis of occupational health programs. Health utility and occupational diseases have not been reported for the university staff in China. In the light of "Healthy China," we conducted this study aiming to (1) estimate the health utility of university staff to inform cost-utility analysis and (2) screen and identify potential occupational diseases for this occupation and examine their impacts on health.MethodsAn occupational health survey was conducted in a sample of working-age university staff. Participants were interviewed face-to-face using the WHO Health and Work Performance Questionnaire and the European Quality of Life 5 Dimensions (EQ-5D) instrument to measure health conditions and health utility, respectively. The univariate analysis included the t-test, chi-square test, and correlation techniques. Multivariate generalized linear models were applied to evaluate the significance of each health condition when controlling for other factors.ResultsThe sample (n = 154) had a mean age of 40.65 years and consisted of slightly more women (51.30%). Participants attained a mean (standard deviation) health utility of 0.945 (0.073). The most affected domain was anxiety/depression with 62 (40.26%) participants reporting problems, followed by pain/discomfort which captured 60 (37.66%) staff with problems. Thus, pain and psychologically related conditions were prevalent. Multivariate models identified two conditions that can significantly reduce the health utility. The psychological/emotional conditions were associated with a utility loss of −0.067 (95%CI: −0.089, −0.045). The pain in body parts other than the head, neck, and back reduced the utility by −0.034 (95%CI: −0.055, −0.014).ConclusionWorking-age staff in Chinese universities may have a lower health utility than the general population. Psychological conditions and musculoskeletal pain appear like occupational diseases. With the health utility data available, economic evaluation of cost-utility should follow up to facilitate the implementation of cost-effective programs.